2013
DOI: 10.6002/ect.2012.0234
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Salvage of a Pancreatic Graft After a Venous Thrombosis: Case Report and Literature Review

Abstract: Simultaneous kidney and pancreatic transplant is the criterion standard for treatment of end-stage renal failure because of diabetic nephropathy. Venous thrombosis occurs in approximately 5% of pancreatic transplants, and it is notoriously difficult to treat, forming the most common nonimmunologic cause of graft loss. We report a case of early detection of pancreatic graft venous thrombosis by measuring urinary amylase, resulting in the successful endovascular salvage of the pancreatic graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…In a study of 47 patients with graft failure, the main indication for pancreatectomy was vascular thrombosis and all patients with graft loss within 14 days of initial surgery required pancreatectomy 47 . Graft salvage may be achievable with prompt diagnosis and treatment 30 ; however, endovascular thrombectomy remains uncommon within the literature, with most studies focusing on the role of anticoagulation 4,14,48 . A study of 188 pancreas transplants evaluated fixed low‐molecular‐weight heparin compared to adjusted unfractionated heparin and demonstrated that fixed‐dose heparin may not be inferior to dose‐adjusted heparin in preventing venous graft thrombosis 49 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study of 47 patients with graft failure, the main indication for pancreatectomy was vascular thrombosis and all patients with graft loss within 14 days of initial surgery required pancreatectomy 47 . Graft salvage may be achievable with prompt diagnosis and treatment 30 ; however, endovascular thrombectomy remains uncommon within the literature, with most studies focusing on the role of anticoagulation 4,14,48 . A study of 188 pancreas transplants evaluated fixed low‐molecular‐weight heparin compared to adjusted unfractionated heparin and demonstrated that fixed‐dose heparin may not be inferior to dose‐adjusted heparin in preventing venous graft thrombosis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Directly, surgery damages the endothelial wall due to clamping and division of vessels, which activates the intrinsic coagulation pathway. Indirectly, surgery causes an inflammatory response, acute graft rejection, and dehydration all of which can precipitate thrombosis 14 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations